PENGARUH DIGITAL CITIZENSHIP TERHADAP ETIKA DIGITAL PESERTA DIDIK DI MAN 2 BANDAR LAMPUNG - Septia Lestari, Indah; Devi Sutrisno Putri; Nurhayati; Yunisca Nurmalisa; Fitra Endi Fernanda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of digital citizenship on the digital ethics of eleventh-grade students at MAN 2 Bandar Lampung. The study employed a descriptive method with a quantitative approach. The research sample consisted of 76 students selected through random sampling. Data were collected using questionnaires and interviews, while data analysis was conducted using simple linear regression analysis. The results showed that digital citizenship had a positive and significant effect on digital ethics, accounting for 42.0%. This effect occurred because students who possessed good digital citizenship tended to be more responsible in interacting and communicating in digital spaces. Students with good digital citizenship were found to have good digital ethics as well, enabling them to demonstrate positive actions or activities in digital environments, such as providing valid information, avoiding hate speech, refraining from insulting others, and maintaining the good reputation of others on social media. Digital citizenship among students was proven to contribute to the strengthening of ethical digital behavior, particularly in communication and interaction within digital spaces or social media. Keywords: Digital Citizenship, Digital Ethics, Students